Rapid thermal processing of GAN-based and ALGAINP-based semiconductors for semiconductor laser applications - Yuan, Shu (2008)
This project aimed (1) to establish the relationship between the processing parameters involved in rapid thermal annealing (RTA) and anodic oxide induced intermixing (AOII) and material properties of semiconductor epitaxial layers, and (2) to establish the relationship between the processing parameters involved in RTA and AOII and device performance of LEDs and laser diodes.